THE EFFECT OF LEARNING STYLES ON JUNIOR HIGH SCHOOL STUDENTS' SPATIAL REASONING IN THREE-DIMENSIONAL GEOMETRY - FATUS ATHO'UL MALIK (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
Spatial reasoning ability is crucial in mathematics learning, particularly in three-dimensional geometry. However, its development faces various obstacles, including limited instructional media and teaching approaches that do not accommodate students' learning style diversity. This study aimed to examine the effect of learning styles (visual, auditory, kinesthetic) on junior high school students' spatial reasoning abilities. A mixed-methods sequential explanatory design was employed, involving 30 ninth-grade students from SMP Bustanul Hikmah Lamongan. Quantitative data were collected through learning style questionnaires and spatial reasoning tests covering spatial perception, spatial visualization, and spatial rotation. Qualitative data were obtained through observations and in-depth interviews with three selected subjects representing each learning style. Quantitative analysis using One-Way ANOVA revealed significant differences in spatial reasoning abilities based on learning styles . Kinesthetic students demonstrated the highest average scores, followed by visual and auditory students. Post Hoc Bonferroni tests indicated that both kinesthetic and visual learning styles were significantly more effective than auditory styles. Qualitative findings revealed distinct characteristics: auditory students relied on internal verbalization and struggled with complex visualizatio, visual students created detailed visual representations but were limited in dynamic transformations, kinesthetic students integrated physical gesture simulation with adaptive strategy flexibility. These findings suggest that geometry instruction should accommodate learning style diversity through varied instructional modalities, appropriate scaffolding, and compensatory strategy training. The use of technology such as virtual manipulatives, 3D animations, and augmented reality is recommended to optimize spatial reasoning development across all learning styles.